Integrasi Budaya Lokal Dalam Pengembangan LKPD Untuk Mewujudkan Gerakan Literasi Sekolah - Ema Butsi Prihastari; Ratna Widyaningrum (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
Abstract The purpose of this research was to develop a Student Worksheet that integrates local wisdom to support the School Literacy Movement. Development research approach and method using ADDIE model namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The stages that can be carried out in this research, the analysis stage, initial product planning, and product development. The researched location at SDN Prawit 1 is located in the Banjarsari subdistrict. Data collection techniques using documentation, questionnaires, interviews, and observations. Data analysis techniques used are LKPD study analysis based on local wisdom, analysis of expert validation results, analysis of observation results, and examination of learners' readability. Data validation questionnaire on local wisdom-based LKPD is analyzed descriptively quantitatively using percentages. The results of research that can be carried out during the covid-19 pandemic show that: 1) LKPD based on local wisdom is very feasible according to media experts with a percentage of 84.375%, 2) LKPD based on local wisdom with a percentage of 88.46% according to the material expert is declared very feasible, 3) according to local wisdom-based LKPD linguists with a percentage of 85.4% declared very feasible, and 4) based on the results of readability of LKPD based on local wisdom by learners obtained a score of 4.4 with very decent results. So, LKPD based on local wisdom with the aim of realizing GLS is very feasible to be disseminated to the field.